The Original Protestant Economic Ethic and Contemporary Chinese Society - Shao Kai Tseng, (Journal of Research for Christianity in China (JRCC), 2025)
Ever since its publication in 1905, Max Weber’s Protestant Ethic and the Spirit of Capitalism has been immensely influential in the fields of sociology, political economics, the sociology of religion, etc. Under the influence of Weber’s description of the relations between capitalism and the Protestant work ethic, especially that of the Puritans, the Christian Right in contemporary Western societies often takes lessaiz-faire capitalism to be a necessary implication of the Protestant understanding of the biblical worldview, while proponents of secular social liberalism often accuses Protestantism of being the source of the social injustices associated with the form of capitalism that idolises wealth. This article is an ad-fontes attempt to recover the original work ethic and economic ethic taught by sixteenth- and seventeenth-century Puritans. The first part of the article offers a discussion of Weber’s important contribution as well as his misunderstandings of Puritan theology and the wider social dimensions of the so-called Puritan movement. The second and main part of the article begins with a delineation of the Protestant notion of the biblical worldview by tracing it to John Calvin’s doctrine of Scripture in contrast to the nature-grace cleavage in medieval scholasticism as demonstrated by Thomas Aquinas’s two Summae. The second subsection then offers a brief recapitulation of Leland Ryken’s works on the original Puritan work ethic, sets forth a basic understanding of the Puritan teaching of the sanctity of work as divine vocation. The third subsection focuses on the Puritan view of the gift of wealth, setting forth the thesis that whereas the various libertarian forms of capitalism stress the notion of private rights in relation to property, ownership, and wealth, the Puritans held to an almost ruthless focus on the notion of individual responsibility in relation to these divine gifts. This subsection presents Puritan teachings on frugality, charity, covetousness, voluntary distribution of wealth, moderation (and the rise of the Middle Class as a result thereof) etc., and ends on an emphatic note on the Puritan understanding of wealth and profit as a means to the end of glorifying and enjoying God. The concluding part of the article places the foregoing discussions in the context of contemporary Chinese society, arguing that although the Protestant Christians have in view an ultimate goal—the glory of God—that contemporary Chinese socialist ideology would deem irrelevant, the Protestant economic ethic can offer significant assistance to the this-worldly cause of Socialism with Chinese Characteristics.